Cardiovascular alterations at different stages of hypertension development during ethanol consumption: Time-course of vascular and autonomic changes - Crestani, Carlos Cesar [UNESP]; Silva, Andreia Lopes da; Scopinho, America A.; Ruginsk, Silvia G.; Uchoa, Ernane T.; Correa, Fernando M. A.; Elias, Lucila L. K.; Antunes-Rodrigues, Jose; Resstel, Leonardo B. M. (Elsevier B.V., 2014)
The aim of the present work was to establish a time-course correlation between vascular and autonomic changes that contribute to the development of hypertension during ethanol ingestion in rats. For this, male Wistar rats were subjected to the intake of increasing ethanol concentrations in their drinking water during four weeks. Ethanol effects were investigated at the end of each week. Mild hypertension was already observed at the first week of treatment, and a progressive blood pressure increase was observed along the evaluation period. Increased pressor response to phenylephrine was observed from first to fourth week. alpha(1)-adrenoceptor protein in the mesenteric bed was enhanced at the first week, whereas beta(2)-adrenoceptor protein in the aorta was reduced after the second week. In the third week, ethanol intake facilitated the depressor response to sodium nitroprusside, whereas in the fourth week it reduced nitrate content in aorta and increased it plasma. The bradycardic component of the baroreflex was impaired, whereas baroreflex tachycardia was enhanced at the third and fourth weeks. AT(1A) receptor and C-type natriuretic peptide (CNP) mRNAs in the nucleus tractus solitarius were increased at the fourth week. These findings suggest that increased vascular responsiveness to vasoconstrictor agents is possibly a link factor in the development and maintenance of the progressive hypertension induced by ethanol consumption. Additionally, baroreflex changes are possibly mediated by alterations in angiotensinergic mechanisms and CNP content within the brainstem, which contribute to maintaining the hypertensive state in later phases of ethanol ingestion. Facilitated vascular responsiveness to nitric oxide seems to counteract ethanol-induced hypertension. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Baroreflex; Vascular reactivity; Adrenoceptor; Nitric oxide; Nitrate; Nucleus tractus solitarius